Isolation of entomopathogenic fungi from Northern Thailand and their production in cereal grains - Mar T.T. (2014)
Spore productivity in six entomopathogenic fungal strains isolated from insect cadavers at four locations in Chiang Mai province was evaluated in five cereal grains: white-rice, wheat, rye, corn and sorghum. According to sequence analysis of the internal transcribed spacer regions of these isolates, they were closely related to Beauveria bassiana (2 isolates), Metarhizium flavoviride (1 isolate), Metarhizium anisopliae (1 isolate), Paecilomyces lilacinus (1 isolate) and Isaria tenuipes (1 isolate). Among all fungal isolates, the maximum amount of spores (530.0 × 10 9 conidia/g) was yielded P. lilacinus CMUCDMT02 on sorghum grain followed by white-rice (399.3 × 10 9 conidia/g). Moreover, the highest number of spore in M. flavoviride was 102.8 × 10 9 conidia/g sorghum whereas white-rice yielded the greatest amount of spore for B. bassiana CMUCDMF03 (141.0 × 10 9 conidia/g) after 60 days incubation. The fungal growth rate was found highest in corn for all strains and rye showed the lowest with the exception of P. lilacinus CMUCDMT02 among the tested grains. Spore viability was over 80 % for all isolates that had been inoculated for 60 days. Fungal conidia suspension of P. lilacinus obtained highest virulence against Bactrocera spp. at a concentration of 1 × 10 6 spore/ml. The strains isolated, exhibited good production of conidia suggesting a promising strategy for the mass production of inoculum as biocontrol agents with low production cost. © 2012 Springer Science+Business Media B.V.